Pengaruh Pendekatan Keras dan Lunak Pemimpin Organisasi terhadap Kepuasan Kerja dan Potensi Mogok Kerja Karyawan - Siti Noor Hidayati (Universitas Proklamasi 45 Yogyakarta, 2016)
Strike wich happened in some companies usualy caused by unsatisfied condition for employee. The strike may inflicts a loss upon the company because it may disturb lead to un achieve of some company goals. Increasing work satisfaction is affected by financial or physical satisfaction (hard approach) and psycological or social satisfaction (soft approach). It was revealed that hard and soft approach showed a significan negative effect on strike potential. It was also concluded that hard approach variable dominanly influenced on strike potential compared to soft approach. It was also concluded that the compoany have implemented the hard and soft approach to minimize the strike potential.